Cytotoxicity analysis of alginate impression materials based red seaweed extract on cultured gingival fibroblast cells - Praharani, Depi; Barid, Izzata; Indahyani, Didin Erma; Probosari, Niken; Lestari, Sri; Sulistiyani, Sulistiyani; Sumono, Agus (Faculty of Dentistry, Universitas Islam Sultan Agung, 2024)
Background: Alginate is an impression material that is widely used in dentistry. Alginate can actually also be obtained from natural materials such as red seaweed. The impression procedure causes the impression material to come into contact with oral tissues including the gingiva. Ideally, the materials used must also meet requirements such as low toxicity or non-toxicity so that tissue damage does not occur. This study aims to analyze the cytotoxicity of alginate impression materials from red seaweed extract in gingival fibroblast cell. Method: This experimental laboratory design using post-test only control group design. The research groups consisted of: sodium alginate extract group, red seaweed extract-based alginate impression material, positive control and negative control. Cytotoxicity was tested on gingival fibroblast cell cultures and the effect was analyzed using the MTT assay. Exposure to gingival fibroblast cell cultures was differentiated in three time durations: 5 minutes, 10 minutes and 15 minutes. Each time duration was repeated three times. MTT-formazan production is a method used to measure cell viability (living cells). The data obtained were statistically analyzed using two-way ANOVA test and Tukey HSD post hoc test. Result: There was no significant difference in the average cell viability between the red seaweed extract-based alginate impression material group and the negative control group at an exposure duration of 5 minutes, which was more than 90%. Conclusion: The red seaweed extract-based alginate impression material has no toxic effect on gingival fibroblast cells at 5 minutes exposure.